STRATEGI PEMBELAJARAN AKIDAH AKHLAK DI MTSN 2 PASER KECAMATAN MUARA KOMAM - Hatmiah Hatmiah (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
A good learning strategy is highly expected in order to achieve the expected learning objectives, especially in learning the moral creed at MTsN 2 Paser, Muara Komam District. Based on this description, the formulation of the problem in this study is what are the learning strategies for aqidah morals at MTsN 2 Paser, Muara Komam District? and the purpose of this study was to determine the learning strategy of aqidah morals at MTsN 2 Paser, Muara Komam District. The subjects in this study were 1 aqidah moral teacher at MTsN 2 Paser, Muara Komam District. The techniques used in data collection are observation, interviews, and documentation. Then processed through the process of data reduction, data display, data verification. Meanwhile, to analyze the data the author uses a qualitative descriptive analysis. After the data has been analyzed, it can finally be concluded that the learning strategy for the moral creed at MTsN 2 Paser, Muara Komam District is illustrated in; 1) The strategies used include expository strategies, inquiry strategies, problem-based strategies, and cooperative strategies. One strategy that is always used is the cooperative strategy. 2) The implementation of the strategy, such as the expository strategy, is seen from the emphasis on the material presented and the delivery looks very detailed or detailed. The inquiry strategy is seen from the emphasis on student understanding. The problem-based strategy is seen from the material presented based on a problem. The cooperative strategy is seen from the closeness of the teacher to the students. 3) The obstacle in implementing the strategy is the difficulty of the teacher of the moral creed in controlling the interests of students who are sometimes interested and sometimes less interested in participating in learning.